Psychological status in the participants of the API ADAD Colombia trial assisted by a comprehensive mental health program during COVID 19 pandemic. (31st December 2021) - Ramos, Claudia; Madrigal, Claudia; Giraldo‐Chica, Margarita; Acosta‐Baena, Natalia; Aponte, Claudia; Aguillon, David; Gómez, Manuela; Espinosa, Alejandro; Madrigal, Lucia; Uribe, Claramonika; Saldarriaga, Amanda; Alzate, Diana; et al.
Abstract: Background: Due to the global SARS‐CoV2 pandemic it has been hard to conduct research, including research related to prevention of neurodegenerative diseases. The Alzheimer's Prevention Initiative (API) Autosomal Dominant Alzheimer's Disease (ADAD) Colombia trial is being conducted in participants with family history of early‐onset dementia due to the PSEN1 E280A mutation who are cognitively unimpaired at baseline. Participants are enduring three stressors: 1) fear of developing dementia; 2) logistic changes to the study caused by the public health emergency due to the pandemic; and 3) concern about getting infected by SARS‐CoV2. Objective: To describe the frequency of new or exacerbated psychological disorders among the participants of the API ADAD Colombia trial assisted by a comprehensive mental health team during the COVID‐19 pandemic. Method: Participants in the API ADAD Colombia trial have free access to psychology and psychiatry services, either in person or through teleassistance, as well as psychoeducational offerings. These mental health services are provided by the site, outside of the study protocol, and are supported by Health and Social plans which were created to support participants' wellbeing during the trial. Descriptive statistics (mean, standard deviation and percentages) were used to analyze characteristics and frequency of mental health issues in the participants. Result: 66 participants (53 women, 80.3%) were treated by the Mental Health Team from March 1 st, 2020 through December 31 st, 2020. Mean age was 44.09 (SD 6.97) y.o. Before and after the pandemic onset, the most common psychological problems were anxiety (before 36.4%, after 63.6%) and depression (before 34.8 %, after 37.9%). From people who received psychological and psychiatric services, 70% vs. 81.6% felt that those services helped them, respectively. Among participants who received psychological vs. psychiatric assistance, 71.4% vs. 86.9% of patients with depression, 70.3% vs 75% of patients with anxiety and 60% vs 76.2% of patients with other disorders, felt the services helped them with these conditions. Conclusion: A comprehensive mental health program immersed in a trial to prevent or treat devastating diseases as dementia, could mitigate the psychological effects of the COVID‐19 pandemic in study participants.